Transient down‐regulation of the RNA silencing machinery increases efficiency of Agrobacterium‐mediated transformation of Arabidopsis. Issue 5 (28th January 2014) - Bilichak, Andriy; Yao, Youli; Kovalchuk, Igor
Summary Agrobacterium tumefaciens is a plant pathogen that is widely used in plant transformation. As the process of transgenesis includes the delivery of single‐stranded T‐DNA molecule, we hypothesized that transformation rate may negatively correlate with the efficiency of the RNA‐silencing machinery. Using mutants compromised in either the transcriptional or post‐transcriptional gene‐silencing pathways, two inhibitors of stable transformation were revealed—AGO2 and NRPD1a. Furthermore, an immunoprecipitation experiment has shown that NRPD1, a subunit of Pol IV, directly interacts with Agrobacterium T‐DNA in planta. Using the Tobacco rattle virus (TRV)‐based virus‐induced gene silencing (VIGS) technique, we demonstrated that the transient down‐regulation of the expression of either AGO2 or NRPD1a genes in reproductive organs of Arabidopsis, leads to an increase in transformation rate. We observed a 6.0‐ and 3.5‐fold increase in transformation rate upon transient downregulation of either AGO2 or NRPD1a genes, respectively. This is the first report demonstrating the increase in the plant transformation rate via VIGS‐mediated transient down‐regulation of the components of epigenetic machinery in reproductive tissue.